2020
DOI: 10.1016/j.tips.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation of BRD4-Degrading PROTAC: Improving Druggability To Target the ‘Undruggable’ MYC in Pancreatic Cancer

Abstract: The continuing quest for better subcutaneously administered prandial insulins: a review of recent developments and potential clinical implications. Diabetes Obes. Metab. 22, 743-754 12. Mann, J.L. et al. (2020) An ultrafast insulin formulation enabled by high-throughput screening of engineered polymeric excipients. Sci. Transl. Med. 12, eaba6676 13. Maikawa, C.L. et al. (2020) Stable monomeric insulin formulations enabled by supramolecular PEGylation of insulin analogues. Adv. Ther. 3, 1900094 14. Kildegaard, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The current ndings con rmed that CRBN expression played an essential role in the sensitivity of T-ALL cells to ARV-825, given that shRNA-mediated knockdown or overexpression of CRBN reduced and increased their sensitivity to ARV-825, respectively. These results indicated that the enhanced antileukemic effect of ARV-825 was closely related to CRBN, consistent with results in other tumors [18,33]. c-Myc is transcriptionally regulated by super-enhancers in several hematological malignancies.…”
Section: Discussionsupporting
confidence: 89%
“…The current ndings con rmed that CRBN expression played an essential role in the sensitivity of T-ALL cells to ARV-825, given that shRNA-mediated knockdown or overexpression of CRBN reduced and increased their sensitivity to ARV-825, respectively. These results indicated that the enhanced antileukemic effect of ARV-825 was closely related to CRBN, consistent with results in other tumors [18,33]. c-Myc is transcriptionally regulated by super-enhancers in several hematological malignancies.…”
Section: Discussionsupporting
confidence: 89%
“…ARV-825 consists of OTX015 and the E3 ubiquitin ligase cereblon (CRBN) used in PROTAC technology via a flexible chemical linker, which could efficiently degrade BRD4 (27). ARV-825 has been studied to treat pancreatic cancer (30,31), vemurafenib-resistant melanoma (32), cholangiocarcinoma (33), thyroid carcinoma (34), acute myeloid leukemia (35,36,38), and neuroblastoma therapy (37). These studies demonstrated that ARV-825 had a more effective inhibition on BRD4 protein.…”
Section: Discussionmentioning
confidence: 99%
“…ARV-825 consists of OTX015 and the E3 ubiquitin ligase cereblon (CRBN) using PROTAC technology, which degraded BRD4 more efficiently ( 27 ). ARV-825 has been studied to treat pancreatic cancer ( 30 , 31 ), vemurafenib-resistant melanoma ( 32 ), cholangiocarcinoma ( 33 ), thyroid carcinoma ( 34 ), and acute myeloid leukemia ( 35 , 36 ). ARV-825 could play a critical role in neuroblastoma therapy ( 37 ) and T-cell acute lymphoblastic leukemia ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of thalidomide's mechanism of action as a cereblon (CRBN) ligand in 2010 suggested a second E3 ligase recruiting moiety for common use ( 64 ) (see Hijacking the UPS: molecular glues section for further elaboration). Indeed, thalidomide and its derivatives (the “phthalimides” or “IMiDs”) have since been used in PROTACs to induce the degradation of numerous target proteins ( 59 , 64 , 65 , 66 , 67 , 68 ). Interestingly, as compared with VHL, the promiscuous CRBN has been shown to be more accepting of neosubstrate degradation thus far ( 69 ).…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%